Mentoring for new secondary Chinese language teachers in the United States. (August 2019) - Wang, Wenxia; Bale, Jeff
Abstract: This study investigates mentoring for four new Chinese language teachers teaching in U.S. K-12 schools. The qualitative collective case study collected data from multiple sources across the teachers' first year of teaching. NVivo 8 was used for coding and analyzing the data. The study finds that mentoring played a critical and facilitating role in the new teachers' learning to teach. However, the varied mentoring practices and different disciplinary and cultural backgrounds between the mentors and the new teachers might have affected more successful mentoring. The findings are discussed and proposals are made for more robust and smooth development of K-12 Chinese education in the United States.